(untitled) (Revista de Educação Continuada em Medicina Veterinária e Zootecnia do CRMV-SP, 2013)
Several species of domestic and wild animals can transmit rabies to men. The epidemiology present different patterns according to each region, and the identification of infected animals has great importance to assist prophylatic measures. The present study consists in a retrospective of animal rabies diagnosis realized by the Zoonoses Diagnosis Service (ZDS), from the Veterinary Hygiene and Public Health Department, located at the School of Veterinary Medicine and Animals Science (FMVZ), São Paulo State University (UNESP), Botucatu city (22°53’09”S 48°26’42”W), Brazil. The ZDS is linked to Pasteur Institute of São Paulo State, contributing to rabies control. Most of the samples submitted to rabies diagnosis (over 95%) come from cities located in the central region of São Paulo State, which is the most populous State of Brazil (around 41,252,160 habitants), has a territory of 248,209.426 km2, and its animal trade has great importance in the national economy. The immunofluorescent antibody test (IFAT) and the bioassay in mice were the laboratorial tests employed for rabies diagnosis. Data were recorded from 2002 to 2011. A total of 5146 samples were analyzed (2,409 bats, 1,669 dogs, 512 cats, 329 bovines, 100 terrestrial wild mammals, 95 horses, 38 sheep, 19 goats and 6 pigs). The species that presented positive diagnosis were bats (n=24), bovines (34), horses (n=6) and pigs (n=1), totalizing 65 positive animals. The proportion of positivity among each species were: 1.0% for bats (24/2409), 10.3% for bovines (34/329), 6.3% for horses (6/95), 16.6% for pigs (1/6) and 0.0% for dogs, cats, sheep, goats and terrestrial wild mammals. The results indicate that bovines, horses and bats are infected by rabies virus in this region. Although the proportion of positive pigs was high (16.6%), only 6 animals were sampled, and a study including a representative number of pig samples could provide a more reliable data, not only for pigs but also for sheep, goats and terrestrial wild mammals. Bats presented a lower proportion of positive animals when compared to bovines and horses. This fact is a result of the high number of bats submitted to rabies diagnosis without clinical suspiciousness of the disease, since any bat found in urban areas by the Environment Health Department of the city is sent to rabies diagnosis. The absent of positive dogs and cats indicates the success of the preventive measures adopted for these species in the last years, especially the municipal vaccination campaigns, whose focus are these animals.